2014
DOI: 10.1111/jcmm.12353
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of microRNA‐21 correlates with the imbalance of Th17 and Treg cells in patients with rheumatoid arthritis

Abstract: The imbalance of Th17/Treg cell populations has been suggested to be involved in the regulation of rheumatoid arthritis (RA) pathogenesis; however, the mechanism behind this phenomenon remains unclear. Recent studies have shown how microRNAs (miRNAs) are important regulators of immune responses and are involved in the development of a variety of inflammatory diseases, including RA. In this study, we demonstrated that the frequencies of CD3+CD4+IL-17+Th17 cells were significantly higher, and CD4+CD25+FOXP3+ Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
133
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(138 citation statements)
references
References 56 publications
(83 reference statements)
4
133
1
Order By: Relevance
“…Defects in CD4 + CD25 + Tregs have been observed in RA patients 16, and Treg plays a pivotal role in the regulation of auto‐reactive T‐cell activation in CIA 29. Our previous study demonstrated that SJMHE1 treatment increases CD4 + CD25 + Tregs in vivo and in vitro 11, as well as generates CD4 + CD25 + Tregs to suppress DTH responses 12.…”
Section: Resultsmentioning
confidence: 98%
“…Defects in CD4 + CD25 + Tregs have been observed in RA patients 16, and Treg plays a pivotal role in the regulation of auto‐reactive T‐cell activation in CIA 29. Our previous study demonstrated that SJMHE1 treatment increases CD4 + CD25 + Tregs in vivo and in vitro 11, as well as generates CD4 + CD25 + Tregs to suppress DTH responses 12.…”
Section: Resultsmentioning
confidence: 98%
“…The identification of novel upstream modulators or downstream targets of the IL-6/STAT3 pathway will provide insight into the involvement of altered miRNA expression in the progression of chronic inflammation. In RA patients, the expression levels of miR-21 were significantly lower and accompanied by increased STAT3 expression and activation (Dong et al, 2014). Moreover, Iliopoulos et al found that miR-21 and miR-181 are rapidly and dramatically regulated during cellular transformation.…”
Section: Il-6 Signaling Pathwaymentioning
confidence: 99%
“…miR-21 is known to be specifically expressed in the Treg subset (13) and promotes Treg differentiation by positively regulating expression of FoxP3 itself, the Treg-specific transcription factor. miR-21 also has the potential to positively regulate Treg activity by directly targeting a proposed negative regulator of TGF-β signaling, SMAD7 (14,15). In contrast, other studies have suggested that miR-21 in fact restrains Treg activity through intrinsic T-reg-specific mechanisms and limiting FOXP3 activity (16) or indirectly by promoting the activity of Th17 cells, whose pro-inflammatory nature counters Treg function (14).…”
mentioning
confidence: 97%
“…For example, rheumatoid arthritis patients, characterized by chronic inflammation in synovial joints, display decreased serum miR-21 levels (15). This is associated with decreased Treg function and an increase in the number and activity of the Th17 subset, promoting chronic inflammation.…”
mentioning
confidence: 99%